Quality of Commercial Coffees: Heavy Metal and Ash Contents - Mariana Teixeira Pigozzi; Flávia Regina Passos; Fabrícia Queiroz Mendes (Journal of Food Quality)
This study aimed to quantify the ash content and to determine the concentration of heavy metals in roasted ground coffee and their respective infusions. The ash content was determined by incineration of the samples, and the quantification of heavy metals was performed by flame atomic absorption spectrophotometry for the following metals: cadmium, lead, copper, chromium, nickel, and zinc. According to the ash analysis, 15% of the roasted ground coffee samples were within the standards established by the legislation of the state of São Paulo, which has set an ash content of below 5%. In the roasted ground coffee samples, the Cd, Cu, Ni, and Zn contents did not exceed the limit established by Brazilian legislation. In several samples, both Pb and Cr were found in high levels, exceeding the limits established by Brazilian legislation. In the infusions of roasted ground coffee, the Cd, Cu, Cr, and Ni contents were below the detection limit of the equipment. Zn was found in all infusions and Pb was only detected in seven coffee infusion samples. Overall, the concentrations of heavy metals found in the commercially roasted ground coffee and their respective infusions are lower than the limits recommended by the official inspection agencies and, thus, are suitable for consumption.